Text messages to improve child diets: Formative research findings and protocol of a randomised controlled trial in Nepal - Kenda Cunningham; Pooja Pandey Rana; Mohammad Masudur Rahman; Aman Sen Gupta; Shraddha Manandhar; Edward A. Frongillo (Wiley, 2023)
Abstract Given the role of malnutrition in childhood morbidity and mortality, the prioritisation of maternal and child nutrition programmes has grown significantly in the 21st century. Policies and programmes aim to improve infant and young child feeding, but questions persist about the most effective combination of interventions to achieve desired behaviour change. There is increasing interest in mobile‐based interventions globally, but scant evidence exists to guide donors, policymakers and programme implementers on their effectiveness. Formative research was conducted to assess the feasibility and acceptance of text message‐based interventions and to guide the final design of the text message intervention. This protocol is for a cluster‐randomised controlled trial to test the effectiveness of adding text messaging to other ongoing SBC interventions to promote egg consumption, dietary diversity and other ideal dietary practices, particularly among children 12-23 months of age in Kanchanpur, Nepal. The trial findings will contribute to the emerging body of evidence on the effectiveness of using text messages for behaviour change, specifically for young child dietary outcomes in South Asia. Recent studies have suggested that mobile‐based interventions alone may be insufficient but valuable when added to other social and behavioural interventions; this trial will help to provide evidence for or against this emerging theory. This trial was registered at ClinicalTrials.gov on 11 March 2019 (ID: NCT03926689) and has been updated twice.